Mixed-Valve Disease: Management of Patients with Aortic Stenosis and Mitral Regurgitation: Thresholds for Surgery Versus Percutaneous Therapies - Jean-Bernard Masson; Jessica Forcillo (US Cardiology Review)
Significant mitral regurgitation (MR), frequently seen in the presence of severe aortic stenosis (AS), results in an association that negatively affects prognosis and imposes particular challenges for both the assessment of the severity of valvular lesions and decisions regarding treatment allocation. This article reviews the available literature with regards to the assessment of MR and AS in the presence of both; surgical management and results in patients with concomitant AS and MR; the effect of MR on outcomes in patients undergoing transcatheter aortic valve replacement; the effect of transcatheter aortic valve replacement on MR severity; and percutaneous treatment for MR after transcatheter aortic valve implantation. The authors aim to provide assistance in the decision-making process to treat patients with either a higher-risk double-valve procedure or a simpler, but perhaps incomplete, single-valve option.